DAMPAK PENINGKATAN PRODUKTIVITAS DAN PERLUASAN AREAL PANEN TERHADAP UPAYA KEMANDIRIAN PANGAN DAN KESEJAHTERAAN PETANI PADI - Prayuningsih, Henik; Haryati, Yuli (Jurnal Sosial Ekonomi Pertanian, 2008)
This research aimed to know : (1) the impact of increasing of productivity to food autonomy and the welfare of paddy farmer in 2020; and (2) the impact of increasing of harvested area to food autonomy and the welfare of paddy farmer in 2020. Research covered national scale, using secondary time series data between 1970 – 2004 with descriptive analytic method. Method of analysis  Two Stage Least Square (2-SLS)  by using Statistical Analysis System (SAS) ver 9.2 program as a software. The Result of this research  shows that  : (1) the impact of increasing of productivity and harvested area in 2020 will  increase  food autonomy but decreasing the welfare of paddy farmer; (2) just  increasing  productivity or harvested area in  2020 will not reach save food autonomy; (3) the combination of  reaching productivity until 5 ton/ha  and increasing harvested area until 10% in 2020 will  reach   food autonomy 90,233%  although  decreasing the welfare is the biggest. Key words : Productivity, Harvested area, Food autonomy, Farmer welfare